Hazard evaluation of box packaging process in food seasoning industry based on SNI 9011:2021 - Muslim, Amalia; Rahdiana, Nana; Nurizzati, Annisa (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
Musculoskeletal disorders (MSDs), known in Indonesia as Gangguan Otot Tulang-Rangka Akibat Kerja (GOTRAK) are one of the most common ergonomic problems in the workplace, caused by poor posture, repetitive movements, and long working hours. These conditions have a negative impact on employee health and productivity and increase healthcare costs for companies. This study aims to analyze the potential for GOTRAK complaints among workers in the box packaging process in the food seasoning industry, in accordance with Indonesian National Standard (SNI) 9011:2021. This study was conducted using a quantitative approach with a Musculoskeletal Disorder Questionnaire to assess MSD complaints. Data were collected through field observation, questionnaire completion, and work posture analysis using the methods outlined in SNI 9011:2021. The research variables included work posture, work duration, and physical strain of the workers. The results of the worker interviews regarding body part complaints showed a high risk level with risk scores of 19 and 20. The most common parts of the body to experience pain were the shoulders, upper back, lower back, and hips. The results of the ergonomic assessment of the upper body in carton packing work gave a score of 38, indicating hazardous conditions that require immediate improvement. In addition, the results of the analysis were used to develop ergonomic-based improvement recommendations to increase safety and comfort in the workplace. It is hoped that this study will provide companies with guidance on how to reduce ergonomic risks in the workplace, improve workers' wellbeing and support the development of a more sustainable industry.